2020
DOI: 10.3390/healthcare9010020
|View full text |Cite
|
Sign up to set email alerts
|

Low Vision Profile in Jordan: A Vision Rehabilitation Center-Based Study

Abstract: The aim of this paper is to study the profile of persons with low vision in Jordan based on the clinical records of service users who attended the Vision Rehabilitation Center (VRC) at the German Jordanian University (GJU). A retrospective study was conducted by reviewing the archived data for persons with low vision attending the VRC over the period September 2012 to December 2017. The information collected included age, gender, referral, geographical distribution, chief functional visual problems, and ocular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 55 publications
(97 reference statements)
1
5
0
Order By: Relevance
“…Another study conducted by the German Jordan University Vision Rehabilitation Centre found that retinitis pigmentosa was the most common cause of visual impairment in patients referred from all over the country. 12 This is consistent with our findings, as both services are based in tertiary centres. Retinitis pigmentosa, as well as other inherited retinal dystrophies like Stargardt disease, is not uncommon in developing countries including Jordan, Malaysia and Nigeria; and although its inheritance is multifactorial, consanguineous marriages play a significant role in its transmission.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Another study conducted by the German Jordan University Vision Rehabilitation Centre found that retinitis pigmentosa was the most common cause of visual impairment in patients referred from all over the country. 12 This is consistent with our findings, as both services are based in tertiary centres. Retinitis pigmentosa, as well as other inherited retinal dystrophies like Stargardt disease, is not uncommon in developing countries including Jordan, Malaysia and Nigeria; and although its inheritance is multifactorial, consanguineous marriages play a significant role in its transmission.…”
Section: Discussionsupporting
confidence: 93%
“…Qutishat et al published an excellent report about the profile of low vision in the Middle Eastern country outlining the clinical measures and barriers pertaining to a centralized low vision service over a five year period. 12 …”
Section: Introductionmentioning
confidence: 99%
“…[11] The relatively high male to female ratio (1.9:1) is also similar to that of other studies conducted in Korea-1.8:1, [12] Malaysia-2.2:1, [13] and Nepal-2.3:1.11 Whereas,a study done at Vision Rehabilitation Center (VRC) in Germany in 2021 found no significant influence of gender and age on ocular pathology distribution. [14] In our study most of the patients belonged to rural population (54%) while only 46% belonged to urban population. Similar to our study, Z. Alotaibi, A. in 2015 in Riyadh reported in their study that rural population is more affected by vision impairment as compared to that of urban population.…”
Section: Discussionmentioning
confidence: 47%
“…The Strengths of this study is mainly the advantages of methodology. Conjoint analysis is an approach of design, data collection, and statistical analysis of research methods, that allows measuring the value that consumers place on products or services formed by combination of different attribute levels [ 19 ]. By using a mathematical analysis method, value can be assigned to each attribute level to evaluate the utility and relative importance of a product or service, and ultimately assess the consumer preference.…”
Section: Discussionmentioning
confidence: 99%
“…These services have been proved to be effective in delaying the deterioration of vision [ 16 , 17 ]. Low vision rehabilitation centers in Germany, Australia and some countries are well developed, can provide comprehensive health management services for patients with VI [ 18 , 19 ]. However, there are few rehabilitation centers for low vision in China, and the health management of patients with VI is mostly managed by hospitals.…”
Section: Introductionmentioning
confidence: 99%